2016
DOI: 10.1371/journal.pgen.1006334
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a Is a Haploinsufficient Tumor Suppressor in CD8+ Peripheral T Cell Lymphoma

Abstract: DNA methyltransferase 3A (DNMT3A) is an enzyme involved in DNA methylation that is frequently mutated in human hematologic malignancies. We have previously shown that inactivation of Dnmt3a in hematopoietic cells results in chronic lymphocytic leukemia in mice. Here we show that 12% of Dnmt3a-deficient mice develop CD8+ mature peripheral T cell lymphomas (PTCL) and 29% of mice are affected by both diseases. 10% of Dnmt3a+/- mice develop lymphomas, suggesting that Dnmt3a is a haploinsufficient tumor suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…To generate conventional Dnmt3b knockout allele, we used approach described previously 21,44,45 utilizing Dnmt3b 2loxP mice obtained from E. Li (Novartis Institutes for Biomedical Research, Cambridge, Massachusetts, USA). we generated Dnmt3a −/− ;Dnmt3b −/− cell line previously 20 .…”
Section: Methodsmentioning
confidence: 99%
“…To generate conventional Dnmt3b knockout allele, we used approach described previously 21,44,45 utilizing Dnmt3b 2loxP mice obtained from E. Li (Novartis Institutes for Biomedical Research, Cambridge, Massachusetts, USA). we generated Dnmt3a −/− ;Dnmt3b −/− cell line previously 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Staci L. Haney et al suggested that Dnmt3a is a haploinsufficient tumour suppressor in CD8 + peripheral T-cell lymphoma. Decreased expression of DNMT3A is related to the downregulation of the tumour suppressor p53, which may also contribute to the pathogenesis of CD8 + PTCL [ 114 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Furthermore, the ectopic introduction of c-Kit variants into a Dnmt3a-deficient background produces acute leukemia [43]. Moreover, DNMT3A inactivation leads to the progression of peripheral T cell lymphoma (PTCL) and lung tumors, thus indicating that DNMT3A may act as a tumor-suppressor gene [44, 45]. Studies have also shown that DNMT3B acts as a tumor suppressor in Myc-induced lymphomas and MLL-AF9-driven AML [46].…”
Section: Emerging Evidence Of Dnmts In Malignant Transformationmentioning
confidence: 99%